2021
DOI: 10.5465/amj.2017.1256
|View full text |Cite
|
Sign up to set email alerts
|

Too Unsafe to Monitor? How Board–CEO Cognitive Conflict and Chair Leadership Shape Outside Director Monitoring

Abstract: Research into boards of directors has provided mixed support for the view that outside directors' independence or leadership by an independent chair improves monitoring. In this study, we use a micro-level approach to provide a better understanding of why outside directors have difficulty in monitoring the CEO. We highlight that an important reason for this lies in the boardroom dynamics associated with (a) outside directors' cognitive conflict with the CEO and (b) the chair's leadership of the board. Our indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 126 publications
6
72
0
Order By: Relevance
“…Using the same keywords and following the same inclusion–exclusion logic, we ran a second search in June 2020 to track missing references and added 14 additional articles to our review database. In the second stage, we conducted three additional searches: the first one used two keywords, “Chair Leadership” and “Chairperson Leadership,” respectively, then used the keywords “Board Leadership” OR “Board Leader.” Among these new keywords, the first one is inspired by the recent article of Veltrop et al (2020), the second is informed by Machold, Huse, Minichilli, and Nordqvist (2011) and Kanadlı, Torchia, and Gabaldon (2018), and the rest is suggested by an independent anonymous reviewer of the journal. To maintain thorough consistency, we used the same exclusion criteria and found 39 articles.…”
Section: Scope Of the Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the same keywords and following the same inclusion–exclusion logic, we ran a second search in June 2020 to track missing references and added 14 additional articles to our review database. In the second stage, we conducted three additional searches: the first one used two keywords, “Chair Leadership” and “Chairperson Leadership,” respectively, then used the keywords “Board Leadership” OR “Board Leader.” Among these new keywords, the first one is inspired by the recent article of Veltrop et al (2020), the second is informed by Machold, Huse, Minichilli, and Nordqvist (2011) and Kanadlı, Torchia, and Gabaldon (2018), and the rest is suggested by an independent anonymous reviewer of the journal. To maintain thorough consistency, we used the same exclusion criteria and found 39 articles.…”
Section: Scope Of the Reviewmentioning
confidence: 99%
“…However, this argument is contested in recent studies, in which scholars suggested that a separate board chair can facilitate greater collaboration with the CEO and other board members, resulting in a better firm performance (Bezemer et al, 2018; Krause, 2017; Morais, Kakabadse, & Kakabadse, 2020). In fact, the authors found that effective board chairs help alleviate board–CEO conflicts, orient board members to more strongly emphasize shareholders' interests, and engage in productive discussions by facilitating a participatory environment (Bezemer et al, 2018; Guerrero, Lapalme, & Séguin, 2015; Shekshnia, 2018; Veltrop et al, 2020). They influence an organization's capacity to achieve goals and build high morale among employees as a result of their organizational awareness (Bailey & Peck, 2013; Y. D. Harrison & Murray, 2012).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…First and most importantly, our empirical analysis does not demonstrate the behavioral mechanisms by which a gender pay disparity influences the TMT's functioning (i.e., male members and female members reduce collaboration; female members withhold their opinions; male members do not take female members' contributions seriously). Information about the TMTs' interpersonal dynamics such as the degree of interaction and collaboration was not available; only a handful of empirical studies have measured TMT‐level phenomena (e.g., McDonald & Westphal, 2003; Veltrop, Bezemer, & Nicholson,, & Pugliese, 2021), and they use cross‐sectional surveys conducted in a limited number of firms 7 . It is very difficult (perhaps even impossible) to measure these mediating mechanisms in combination with longitudinal archival data like ours.…”
Section: Discussionmentioning
confidence: 99%
“…Bezemer et al (2014) videotape six board meetings and use the data collected to analyse various aspects of board processes, including patterns of director interactions (Pugliese et al, 2015), habitual accountability routines (Nicholson et al, 2017), the influence of board chairs (Bezemer et al, 2018). Veltrop et al (2021) videotape seven board meetings of five Australian companies to analyse CEOboard cognitive conflict and chair leadership. Adopting a similar method, Pernelet & Brennan (2021a, 2021b video-Introduction to Special Issue on Innovations in Research Methods in Accounting and Governance tape nine board meetings to study non-executive directors' and managers' question-and-answer interactions.…”
Section: Governancementioning
confidence: 99%